168. Intradermal Immunization Drives Humoral and Cellular Immunity to the Lung and Protects Against Acute P. aeruginosa Pneumonia. (26th November 2018) - Baker, Sarah; Morici, Lisa
Abstract: Background: Pseudomonas aeruginosa is a leading cause of hospital-associated pneumonia, with 6, 700 multidrug-resistant infections in the US annually. Evidence suggests that antibodies and CD4 Th1 and Th17 responses contribute to protection against P. aeruginosa infection. Recent work suggests that intradermal (ID) immunization with a vaccine adjuvanted with a double mutant of E. coli heat-labile toxin (dmLT) can direct protective immune responses to mucosal tissues such as the lungs. We sought to determine whether ID immunization with P. aeruginosa outer membrane proteins (OMPs) with dmLT could drive migration of CD4+ T cells and antibodies to the lungs and protect against P. aeruginosa pneumonia. Methods: We immunized C57Bl/6 mice with 1 µg of OMPs with 1 µg dmLT. Control mice received OMPs or saline. Antibody and T-cell responses were assessed by ELISA and flow cytometry, respectively. We then evaluated the protective efficacy of the vaccine in a lethal acute pneumonia model. Immunized mice were challenged with 7 × 10 6 CFU of P. aeruginosa via oropharyngeal aspiration into the lungs. Finally, we examined whether memory CD4+ T cells was essential for protection by depleting immunized mice of vaccine-induced memory CD4+ T cells. Results: Mice immunized with OMPs and dmLT had a significantly greater concentration of anti-pseudomonal IgG in the serum and lungs and a significantly greater proportion of CD4+ T cells in the lung producing IFN-γ or IL-17A than mice immunized with OMPs alone or saline. ID immunization provided significant protection against P. aeruginosa pneumonia, with 78% of immunized mice surviving compared with 100% mortality in saline immunized controls. Memory CD4+ T-cell–depleted mice displayed reduced survival (40%) compared with nondepleted mice (80%), confirming that memory CD4 T+ cells contribute to OMP-dmLT vaccine-mediated protection. Conclusion: These results demonstrate that ID vaccination against P. aeruginosa protects against acute lethal P. aeruginosa pneumonia by stimulating antigen-specific IgG and Th1- and Th17-type CD4+ memory T cells in the pulmonary milieu. ID immunization with dmLT may reduce the global morbidity and mortality caused by multidrug-resistant respiratory pathogens. Disclosures: All authors: No reported disclosures.